Hemoporfin photodynamic therapy for port-wine stains in children: a prospective study - Jun Cheng; Hanxiang Bai; Hua Yuan; Yun Zou; Mengyu Huang; Zhiping Wu; Ronghua Fu (Frontiers in Medicine, 2026)
Introduction Hemoporfin photodynamic therapy is a promising treatment for port-wine stains. However, its efficacy and safety in pediatric cases remain controversial. This study investigated the efficacy and safety of porphyrin photodynamic therapy for treating port-wine stains in children. Methods In this prospective study, 140 children with port-wine stains were included and all patients received hemoporfin photodynamic therapy at least twice. Their demographic characteristics, treatment outcomes, and adverse events were recorded. Results After two treatment sessions, 79.3% of pediatric patients demonstrated a response. The response rate was significantly higher in patients under 6 years old than those aged 12–18 years. The response rate for the red variant of PWS was significantly higher than that for the purple variant. The response rate in the limbs was markedly lower than that in the face. However, gender, prior PDL treatment history, lesion size exceeding 30 cm 2 , or treatment intervals longer than 6 months did not affect efficacy. All patients tolerated most adverse reactions well. Conclusion Hemoporfin photodynamic therapy is an effective and safe treatment for port-wine stains. Patients with the red type, facial involvement, and those under 6 years of age demonstrate superior efficacy.